Antioxidant activity test of ethyl acetate total extract from Batak leeks (Allium chinense G. Don) - Aliyah Fahmi; Hamelasari Sitompul (Jurnal Pendidikan Kimia (JPKim), 2019)
The research with titled "Antioxidant activity test of ethyl acetate total extract from Batak leeks (Allium. chinense G. Don)" had been done. For the antioxidant activity test using UV Visible Spectrophotometer with 2,2-diphenyl-1-picrylhydrazyl (DPPH) as a scavenging agent obtained IC50 ethyl acetate extract total batak leeks amounted to 52.39% mg / L which stated that the extract was strong antioxidant.Keywords:Activities; antioxidants; Batak leeks